2004
DOI: 10.1267/ahc.37.227
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Communication within the Rat Anterior Pituitary: Immunohistochemical Study on the Relationship between the Hypothalamus, Agranular Cells and GnRH Neurons in the Pars Tuberalis and Anterior Pituitary Gland

Abstract: The pars tuberalis has been generally understood as a simple forward elongation of the glandular pituitary that develops into an architecturally similar structure. In rats, it is also believed that the pars tuberalis completely encircles the infundibular stalk at the ventral portion of hypothalamus. Intact Wistar-Imamichi rats were used in the present study, and frontal and sagittal serial sections of the pituitary gland/brain complex were prepared. Serial sections were stained with hematoxylin-eosin and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…There are numerous reports describing localization, morphological characteristics, gene expression, and/or regulation to the gonadal–pituitary axis of LH‐RH and LH‐RH neurons (Barry and Carette, 1975; Naik, 1975a, b; Setalo et al, 1975; Siverman and Krey, 1978; Ibata et al, 1979; Rethelyi et al, 1981; Kelly et al, 1985; Foster and Youngai, 1991; Nakazawa et al, 1991; Oka and Ichikawa, 1992; D'Este et al, 2000; Yanagisono et al, 2001; Mabuchi et al, 2004; Kurita et al, 2004). Oka and Ichikawa (1992) reported the nonsynaptic release of LH‐RH in fresh fish brain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are numerous reports describing localization, morphological characteristics, gene expression, and/or regulation to the gonadal–pituitary axis of LH‐RH and LH‐RH neurons (Barry and Carette, 1975; Naik, 1975a, b; Setalo et al, 1975; Siverman and Krey, 1978; Ibata et al, 1979; Rethelyi et al, 1981; Kelly et al, 1985; Foster and Youngai, 1991; Nakazawa et al, 1991; Oka and Ichikawa, 1992; D'Este et al, 2000; Yanagisono et al, 2001; Mabuchi et al, 2004; Kurita et al, 2004). Oka and Ichikawa (1992) reported the nonsynaptic release of LH‐RH in fresh fish brain.…”
Section: Discussionmentioning
confidence: 99%
“…Oka and Ichikawa (1992) reported the nonsynaptic release of LH‐RH in fresh fish brain. Only few reports, however, referred to the existence of LH‐RH–positive nerves in the pars tuberalis (Naik, 1975a; Yanagisono et al, 2001; Mabuchi et al, 2004; Kurita et al, 2004). Of these, only Kurita et al (2004) and Mabuchi et al (2004) found by electron microscopy direct entry of the neuroendocrine fiber into the pars tuberalis of pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells construct unique topography caused by homologous and heterologous interactions between cell types and between cells and extracellular matrix [7,11,12]. Junctional complexes have been identified among folliculo-stellate cells [10,18]. On the other hand, observations of the intercellular space among hormone-producing cells have very rarely indicated the presence of desmosomes among prolactin-producing cells [17].…”
Section: Introductionmentioning
confidence: 99%